Cognitive and movement measures reflect the transition to presence-at-hand. (April 2017) - Dotov, Dobromir; Nie, Lin; Wojcik, Kevin; Jinks, Anastasia; Yu, Xiaoyu; Chemero, Anthony
Abstract: The phenomenological philosopher Martin Heidegger's proposed transition from readiness-to-hand to presence-at-hand and the hypothesis of extended cognition were addressed empirically in an experiment on tool use. It involved a video game of steering erratically moving objects to a target while performing a secondary cognitive task. A strong perturbation of the hand-pointer linkage in the video game induced the transition from ready-to-hand to present-at-hand. In Experiment 1, this perturbation resulted in decreased motor performance and improved recall of task-irrelevant features. Experiment 2 replicated these results and addressed additional questions. Measures of movement variability based on the multifractal formalism confirmed the hypothesized decrease in functional integration of the tool during the perturbation. Dynamical interactions allow user and tool to act as a system. The tool is properly described as ready-to-hand during normal operation but as present-at-hand during perturbation. Physiological measures showed that the ready-to-hand to present-at-hand transition does not necessarily lead to a stress response.